Evaluation of Respiratory Emissions During Labor and Delivery: Potential Implications for Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Issue 4 (October 2021) - Mok, Thalia; Harris, Elijah; Vargas, Andres; Afshar, Yalda; Han, Christina S.; Karagozian, Ann; Rao, Rashmi
Abstract : OBJECTIVE: To characterize respiratory emissions produced during labor and vaginal delivery vis-à-vis the potential for transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). METHODS: Observational study of three women who tested negative for SARS-CoV-2 and had uncomplicated vaginal deliveries. Using background-oriented schlieren imaging, we evaluated the propagation of respiratory emissions produced during the labor course and delivery. The primary outcome was the speed and propagation of breath over time, calculated through processed images collected throughout labor and delivery. RESULTS: In early labor with regular breathing, the speed of the breath was 1.37 meters/s (range 1.20–1.55 meters/s). The breath appeared to propagate faster with a cough during early labor at a speed of 1.69 meters/s (range 1.22–2.27 meters/s). During the second stage of labor with Valsalva and forced expiration, the propagation speed was 1.79 meters/s (range 1.71–1.86 meters/s). CONCLUSION: Labor and vaginal delivery increase the propagation of respiratory emissions that may increase risk of respiratory transmission of SARS-CoV-2. Abstract : Respiratory emissions during labor and vaginal delivery demonstrate high propagation speeds, specifically during Valsalva, which highlights the potential increased risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission.